Inverted orientation improves decellularization of whole porcine hearts. (February 2017) - Lee, Po-Feng; Chau, Eric; Cabello, Rafael; Yeh, Alvin T.; Sampaio, Luiz C.; Gobin, Andrea S.; Taylor, Doris A.
Graphical abstract: Abstract: In structurally heterogeneous organs, such as heart, it is challenging to retain extracellular matrix integrity in the thinnest regions (eg, valves) during perfusion decellularization and completely remove cellular debris from thicker areas. The high inflow rates necessary to maintain physiologic pressure can distend or damage thin tissues, but lower pressures prolong the process and increase the likelihood of contamination. We examined two novel retrograde decellularization methods for porcine hearts: inverting the heart or venting the apex to decrease inflow rate. We measured flow dynamics through the aorta (Ao) and pulmonary artery (PA) at different Ao pressures and assessed the heart's appearance, turbidity of the outflow solutions, and coronary perfusion efficiency. We used rectangle image fitting of decellularized heart images to obtain a heart shape index. Using nonlinear optical microscopy, we determined the microstructure of collagen and elastin fibers of the aortic valve cusps. DNA, glycosaminoglycan, and residual detergent levels were compared. The inverted method was superior to the vented method, as shown by a higher coronary perfusion efficiency, more cell debris outflow, higher collagen and elastin content inside the aortic valve, lower DNA content, and better retention of the heart shape after decellularization. To our knowledge, this is the first study to use flow dynamics in a whole heart throughout the decellularization procedure to provide real-time information about the success of the process and the integrity of the vulnerable regions of the matrix. Heart orientation was important in optimizing decellularization efficiency and maintaining extracellular matrix integrity. Statement of Significance: The use of decellularized tissue as a suitable scaffold for engineered tissue has emerged over the past decade as one of the most promising biofabrication platforms. The decellularization process removes all native cells, leaving the natural biopolymers, extracellular matrix materials and native architecture intact. This manuscript describes heart orientation as important in optimizing decellularization efficiency and maintaining extracellular matrix integrity. To our knowledge, this is the first study to assess flow dynamics in a whole heart throughout the decellularization procedure. Our findings compared to currently published methods demonstrate that continuous complex real-time measurements and analyses are required to produce an optimal scaffold for cardiac regeneration.